A comparative analysis of the patient characteristics and cost of managing intravenous drug users (IVDU) with soft tissue abscesses with non-IVDU. Issue 1 (February 2016) - Chotai, N.; Gallagher, K.; Kieffer, W.K.M.; Rogers, B.A.; Ricketts, D.M.
Abstract: Background: Intravenous drug users (IVDU) often present to hospitals with complex co-morbidities, associated with prolonged in-patient admissions. The aim of this study was to compare a cohort of IVDU patients with soft tissue abscesses with non-IVDUs. We analysed the demographics, comorbidities, location of abscesses, multidisciplinary input and financial costs of managing both groups. Methods: A retrospective cohort study was conducted between January 2010 and September 2013. Two age and sex matched cohorts were compared: IVDU and non-IVDU. Results: We identified 44 IVDU patients and 54 non-IVDU patients. The IVDU had higher rates of smoking (89% p  < 0.001) and unemployment (73% p  < 0.05). The most common comorbidities in the IVDU cohort were hepatitis C (17%) and HIV (14%), whereas diabetes mellitus (15%) and hypertension (11%) were the most common in the non-IVDUs ( p  < 0.01). The most common location for an abscess in non-IVDU patients was the hand, whereas IVDU patients had abscesses in their groin. Groin injecting led to a referral to multiple specialties. The median length of stay for the IVDU patients was 4 days and for non-IVDU patients 1 day ( p  < 0.01). The average cost of managing IVDU patients in our unit was £1280: for non- IVDU the cost was £530 ( p  < 0.001). Conclusions: IVDU patients with soft tissue abscesses have higher rates of smoking, unemployment, infection with hepatitis C and HIV compared to a control group. We have suggested several recommendations to optimise the management of these patients including the implementation of an additional code to compensate for the complexity of their management.